The Influence of Transparency in Personalized Recommendation Ads on Consumer Privacy Concerns and Purchase Intentions - Ralph S. H. Böhler (Law and Economy, 2024)
This paper examines the impact of transparency in personalized recommendation advertisements on consumer privacy concerns and purchase intentions in Germany. As personalized ads become increasingly prevalent, consumers express heightened concerns about data privacy. The study utilizes survey data collected from 400 German consumers to analyze the relationship between perceived transparency, trust, and consumer behavior. Findings reveal that transparency significantly reduces privacy concerns and enhances purchase intentions by fostering trust. Consumers highly value transparency features such as data control options, clarity of information, and the ability to opt out. Comparative analysis across international markets shows that Germany leads in transparency practices and consumer trust levels, influenced by stringent data protection regulations like the GDPR. This paper highlights the critical role of transparency in balancing personalization and privacy, providing strategic insights for businesses to optimize their advertising strategies in a privacy-conscious market. By prioritizing transparency, companies can build stronger consumer relationships, increase brand loyalty, and gain a competitive advantage.